Kommentar zu Nietzsches : "Der Antichrist", "Ecce homo", "Dionysos-Dithyramben", "Nietzsche contra Wagner" - Sommer, Andreas Urs (Historischer und kritischer Kommentar zu Friedrich Nietzsches Werken ;, 2013)
The last posthumous manuscripts from 1888 bear witness to an enormous stylistic and intellectual radicalization. The Antichrist purports to be a total "reevaluation of all values." In Ecce homo, Nietzsche explores the genealogy of his own thinking, opening up new dimensions of self-reflection. Nietzsche contra Wagner sums up the many years of Nietzsche's continuing critique of Wagner, while the Dionysian Dithyrambs seek to breathe new life into lyric poetry